Strut waviness and load orientation affected fracture toughness knockdown in biaxially woven square lattices - Kueh, A.B.H.; Kho, V.T. (Elsevier B.V., 2019)
Material imperfection, especially struts waviness attributed to fabrication and service phase, may cause the decay of the fracture resistance of lattice structures. Accordingly, a cautionary step must be taken to ensure the correct fracture properties are employed in the analysis and design of lattices before further utilized in applications. Hence, strut waviness effects on the fracture toughness, KC, of square lattices with respect to numerous loading orientations are of concern in this paper. To examine these effects, square lattices with struts in flat (planar) and biaxially woven configurations are numerically considered. KC is assessed by introducing plane-tension to centrally-cracked lattices for various relative densities ( = 0.05, 0.1, 0.15, and 0.2) and loading directions (α = 0°–90°). In all cases, KC of planar lattices are greater than those woven, with as high as 91.7% of performance knockdown in the latter due to the waviness and loading direction effects. In general, KC correlates directly with relative density but inversely with loading direction. KC enhancement is greater in planar lattices compared to those woven when the relative density is increased. Both lattices exhibit anisotropic KC, in which the effects on the planar lattices are more evident. Failure modes of both lattices are found to be independent of relative density but greatly influenced by loading orientations. A shifting in failure mode from plane-tension to plane-shear can be noticed in accordance with the transition angle α = αt as the loading orientation increases.